Discontinuation of biologic therapy in severe asthma: Evidence and strategies for safe withdrawal: A scoping review - Johanna Ramirez-Villamizar, MD; Ciro D. Ibarra-Enríquez, MD; Juan Sebastián Galindo-Sánchez, MD; Carlos Serrano-Reyes, MD; Liliana Fernández-Trujillo, MD (World Allergy Organization Journal)
Introduction: Severe asthma is characterized by poor disease control despite the use of high-dose inhaled corticosteroids and long-acting bronchodilators. Biologic therapies have revolutionized its management, allowing some patients to achieve remission. However, uncertainty remains regarding the optimal duration of treatment and the safest strategies for discontinuation. This study reviews the available evidence on the withdrawal of biologic therapy in patients with severe asthma in remission, evaluating their clinical outcomes. Methods: A literature review was conducted in PubMed, EMBASE, Epistemonikos, and LILACS up to May 2024, using terms related to severe asthma and discontinuation of biologic therapies. Studies evaluating asthma control after dose reduction or withdrawal of biologic treatment were included, considering outcomes such as exacerbations, lung function, and inflammatory biomarkers. Results: Of the 2494 studies identified, 23 articles were included after full-text review. Discontinuation of tezepelumab led to a gradual loss of clinical control in most patients, although baseline levels of inflammation were not reached. Regarding mepolizumab, 59% of patients experienced at least 1 significant exacerbation within the first year after withdrawal, suggesting the need for prolonged use. For omalizumab, results were heterogeneous: 67% of patients who continued treatment remained exacerbation-free, compared to 47.7 of those who discontinued it. Studies that implemented gradual tapering strategies showed higher success rates in discontinuation without loss of clinical control. Conclusion: Evidence suggests that discontinuation of biologic therapy should be individualized, and a minimum treatment duration of 5 years may be appropriate before considering withdrawal. Optimal candidates include those with sustained clinical control, stable lung function, suppressed inflammatory biomarkers, and no need for oral corticosteroids. Gradual decreasing strategies may optimize treatment withdrawal while minimizing the risk of relapse.